Structural wood design examples (McGraw-Hill's AccessEngineeringLibrary, 2019)
2015/2018 Structural Wood Design Examples is intended to aid instruction in structural design of wood structures using both Allowable Stress Design (ASD) and Load and Resistance Factor Design (LRFD). It contains over 20 design examples and complete solutions for wood member design, connections, and shear walls. Solutions have been developed based on the 2015 and 2018 National Design Specification?(NDS?) for Wood Construction, and the 2015 Special Design Provisions for Wind and Seismic (SDPWS), as appropriate. References are also made to the 2015 and 2018 Wood Frame Construction Manual (WFCM) for One- and Two- Family Dwellings.